Peranan Mashlahah Mursalah dan Pembaharuan Hukum Islam di Indonesia - Barmawi Mukri (Universitas Islam Indonesia, 2003)
The concept of mashlahah mursalah (unrestricted interests) is among the most popular models of classical legal reasoning. This because, the reasons accommodated in this legal reasoning is the consideration to gain the good and avoid the bad in human life. Therefore, compared to others, according to the writer, mashlahah is the most suitable and relevant legal reasoning to implement in Indonesian Islamic legal reform.